2017
DOI: 10.1016/j.eururo.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations in the Molecular Subtypes of Bladder Cancer: Illustration in the Cancer Genome Atlas Dataset

Abstract: Context Recent whole genome mRNA expression profiling studies revealed that bladder cancers can be grouped into molecular subtypes, some of which share clinical properties and gene expression patterns with the intrinsic subtypes of breast cancer and the molecular subtypes found in other solid tumors. The molecular subtypes in other solid tumors are enriched with specific mutations and copy number aberrations that are thought to underlie their distinct progression patterns, and biological and clinical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(139 citation statements)
references
References 85 publications
(173 reference statements)
6
128
0
1
Order By: Relevance
“…For Ba/Sq tumours, as shown previously 26 , the most frequently mutated genes were TP53 (P=5.8x10 -4 ), NFE2L2 (P=0.002) and RB1 (P=0.002). Aggregated mutation data revealed that 58% (134/232, P=0.009) and 20% (43/224, P=0.007) of Ba/Sq tumours contained mutations in TP53 and RB1, respectively.…”
Section: Genomic Alterations Associated With the Consensus Molecular supporting
confidence: 80%
“…For Ba/Sq tumours, as shown previously 26 , the most frequently mutated genes were TP53 (P=5.8x10 -4 ), NFE2L2 (P=0.002) and RB1 (P=0.002). Aggregated mutation data revealed that 58% (134/232, P=0.009) and 20% (43/224, P=0.007) of Ba/Sq tumours contained mutations in TP53 and RB1, respectively.…”
Section: Genomic Alterations Associated With the Consensus Molecular supporting
confidence: 80%
“…ERCC2 mutation prevalence is similar in BASQ-like and non-BASQ-like tumours (8). RB1 mutations -but not deletions -are significantly more common in BASQ-like than in urothelial tumours.…”
Section: Discussionmentioning
confidence: 79%
“…However, deletions are more common in the Lund "genomically unstable" subgroup. There is insufficient data to indicate whether ATM and FANCC alterations are enriched in any taxonomical types (8,10), suggesting that combined mutational analysis and tumour subtyping could increase the ability to predict NAC response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no association with either aggressive or non‐aggressive cancers and no significant heterogeneity in the association by tumour aggressiveness. While genetic studies have suggested that bladder cancer can be classified into more specific molecular subtypes, we were not able to examine this due to lack of data on tumour genotype.…”
Section: Discussionmentioning
confidence: 99%